Results of molecular genetic screening of mutations in the NLRP3, TNFRSF1A, and MVK genes in patients with autoinflammatory diseases and systemic juvenile arthritis - S. O. Salugina; E. A. Kamenets; E. S. Fedorov; E. Yu. Zakharova; M. I. Kaleda (Современная ревматология)
Autoinflammatory diseases (AIDs) are being intensively studied. Molecular genetic testing of patients is of great importance for the diagnosis of AIDs since the basis for its development is pathological mutations that cause innate (antigen-nonspecific) immunity system disorders and the development of inflammation. This also applies to patients with systemic juvenile arthritis (SJA) that has been recently assigned to a group of AIDs due to the great similarity of symptoms. In this connection, the assumption that monogenic AIDs mask SJA in a number of patients was well founded. More than 25 genes, mutations in which lead to AIDs, are known; the NLRP3, TNFRSF1A, and MVK genes are most common and well investigated. These genes cause major monogenic AIDs, such as cryopyrin-associated periodic syndromes (CAPS), TNF receptor-associated periodic syndrome (TRAPS), and hyperimmunoglobulinemia D/deficit mevalonate kinase syndrome (HIDS).Objective: to identify patients with monogenic AIDs among those with fever, arthralgias, and other manifestations of systemic inflammatory response, including among those with SJA, through molecular genetic testing.Patients and methods. In 2012–2016, molecular genetic testing for mutations in the NLRP3, MVK, and TNFRSF1A genes was carried out within the framework of screening in 184 patients (94 women and 90 men). The investigation enrolled 117 patients with suspected AIDs (Group 1) and 67 patients with SJA (Group 2). The selection criteria were periodic or persistent fever, clinical manifestations of systemic inflammatory response (skin rashes, arthralgias/arthritis, lymphadenopathy, hepatolienal syndrome, serositis, etc.), acute-phase markers when excluding infectious, oncohematologic, and autoimmune causes. SJA was diagnosed based on the ILAR criteria (2001). The patients' age ranged from 6 months to 60 years (mean age, 9.0 years [5; 15]), disease duration, 2 months to 54 years (mean duration, 3.0 [1.0; 8.5])). To identify familial aggregation, genetic tests were also carried out in 18 relatives of the patients with genetically verified AIDs. Molecular genetic analysis was performed in the Laboratory of Hereditary Metabolic Diseases, Research Center of Medical Genetics, Moscow.Results. 15 variants of pathogenic mutations in the studied genes were identified in 43 (23.4%) patients: 31 (16.8%) patients with those in NLRP3, 10 (5.4%) in TNFRSF1A (in a heterozygous state), and 2 (1.1%) in MVK (in a compound heterozygous state). In the AID group, the mutations were detected in 31 (26.5%) patients: 24 (20.5%) in NLRP3, 1 (0.9%) in MVK, and 6 (5.1%) in TNFRSF1A. In the SJA group, the mutations were present in 12 (17.9%) patients: 7 (10.4%) in NLRP3, 1 (1.5%) in MVK, and 4 (5.9%) in TNFRSF1A. The most common mutations in the NLRP3 gene were substitution-missense c. 1049C>T (p.T350M) in 7 (25.9%) patients and low-penetrance mutation c. 2113C>A (p. Q705K) in 13 (28.3%). Examinations established the genetic diagnoses of CAPS in 19 (10.3%) patients, TRAPS in 9 (4.9%), and HIDS in 2 (1.1%). In Group 1, CAPS was identified in 17 (14.5%) patients, of whom 15 had Muckle-Wells syndrome (MWS) and 2 had CINCA/NOMID (Chronic infantile neurologic, cutaneous articular syndrome (CINCA)/Neonatal onset multisystem inflammatory disorder (NOMID); TRAPS and HIDS were present in 6 (5.1%) and 1 (0.9%) patients, respectively. In Group 2, there was CAPS (MWS) in 2 (2.9%) patients, TRAPS in 3 (4.5%), and HIDS in 1 (1.5%). Eleven of the 18 relatives of the patients were ascertained to have mutations and 7 were diagnosed as having AIDs (CAPS in 4, TRAPS in 3).Conclusion. About one-quarter of the patients who have an inflammatory phenotype, including the manifestations of SJA, suffer from monogenic AIDs. Half of them received therapy with the interleukin-1 inhibitor canakinumab, which had a pronounced positive effect. Interpretation of the diagnostic value of low-penetrance mutations is hampered and requires an individual approach. The diagnosis of AIDs should be established in patients having no mutations with great caution, in this case, there is a need for clinical and laboratory criteria for the disease and a thorough assessment of the data of medical history of the patient, and his/her family in particular. The decision to assign these patients to receive lifetime expensive targeted therapy should be well justified.